The Role of Artificial Intelligence in Learning English for Business material: Challenges and Ethical Considerations: English - Syamsinar; Marwah Juwita Yusuf; Kapriani; Indrayani Simpuruh; Ray Suryadi; Khaerati; Muh. Amir (JOEY: Journal of English Ibrahimy, 2026)
This study investigated the role of AI tools in English for Business learning, identifies the challenges students face when using these tools, and proposes ethical considerations for their academic use. The researcher employed a descriptive qualitative research design and used purposive sampling to select the participants. The participants consisted of 104 students from STIE Tri Dharma Nusantara. The additional participants were four English lecturers, who discussed the challenges of students’ use of AI from their perspectives and offered consideration for ethical AI use in academic contexts. Data were collected through classroom observations, questionnaires, and semi-structured interviews with 6 students. The findings revealed that AI tools play four major roles in English for Business learning: facilitating effective and efficient learning processes, enhancing business communication competencies, serving as references and models, and acting as catalysts for learning rather than substitutes for educators. Survey results indicate moderate to high levels of AI usage among students. However, several challenges were identified, including unnatural or overly general language output, limited contextual and cultural understanding, reduced critical thinking, increased risk of plagiarism, diminished learning motivation, and lower self-confidence. Lecturers highlighted issues related to the similarity of students’ work and the difficulty in assessing genuine understanding. In response, this study emphasizes the importance of ethical AI integration through effective prompt design and positioning AI as a supportive learning assistant grounded in students’ prior knowledge.